Socially anxious and confident men interact with a forward virtual woman: an experimental study. - Xueni Pan; Marco Gillies; Chris Barker; David M Clark; Mel Slater (PLoS ONE)
Background Male volunteers entered an immersive virtual reality that depicted a party, where they were approached by a lone virtual woman who initiated a conversation. The goal was to study how socially anxious and socially confident men would react to this event. Interest focused on whether the socially anxious participants would exhibit sustained anxiety during the conversation or whether this would diminish over time, and differ from the responses of the more socially confident men. Methodology The scenario was a party with five virtual characters, four sitting at a distance from the participant and talking amongst themselves and one lone woman standing closer. The woman approached the participant, introduced herself and initiated a conversation that was first about mundane matters and then became more personal and intimate. Participants were men who were either relatively socially confident (18) or socially anxious in their relationships with women (18). A second experimental factor was whether or not the other four characters occasionally looked towards the participant. There was a post-trial questionnaire about social anxiety in relation to the experience, and skin conductance and ECG physiological measures were recorded. Our expectation was that the socially anxious participants would show greater anxiety throughout. Conclusions Compared to baseline readings both socially confident and socially anxious groups on average showed signs of significantly increased stress at the initial approach of the virtual woman. The stress then diminished once the conversation entered into the mundane phase and then did not significantly change. Comparing pre- and post-questionnaire anxiety scores there was no change for the more confident participants but a significant decrease in average score amongst the anxious group. The methodology of placing socially anxious participants in a virtual reality where they can gain experience of how to act in a stressful situation promises a novel way forward for treating social anxiety.